Estudo numérico do superaquecimento nos tubos de uma caldeira de queima tangencial simultânea com gás natural e metanol - Santos Neto, João Coringa dos (2018)
The numerical study of the reactive flow within a tangential firing boiler, to investigate the phenomenon of overheating in the furnace wall tubes, was developed in the present work. The capacity of the simulated boiler is 255 t/h of superheated steam, co-firing natural gas and methanol in 20 burners distributed on the corners of the furnace four sides. The flow in each burner was simulated in detail and the velocity, temperature and pressure profiles at the outlets were imported into the furnace. The numerical approach involved the use of the SST − , Eddy Dissipation Concept and Discrete Ordinate models to describe the turbulent reactive flow and the radiation heat transfer. The multiphase atomization process of the liquid methanol with compressed air was treated by the Mixing Model. Images with temperature data inside the furnace were collected by video camera with pyrometer measurement for comparison with numerical results. Finally, the overheating regions were identified.